Chronic eosinophilic pneumonia. Issue 8 (August 1980) - Fox, B; Seed, W A
Abstract : We described three cases of eosinophilic pneumonia of unknown aetiology investigated clinically and by lung biopsy. The illnesses lasted between six and 20 weeks and consisted of cough, dyspnoea, malaise, and in two cases prolonged pyrexia. All had blood eosinophilia and chest radiographs showing widespread bilateral shadowing; in two cases this had a characteristic peripheral distribution. One patient recovered spontaneously and the other two responded to steroids, with disappearance of pyrexia within 12 hours and radiological clearing within 14 days. Lung function tests during the acute illness showed volume restriction or gas transfer defects or both in two cases. After remission all three showed abnormalities if small airways function. Lung biopsies performed during the acute illness were examined histologically and by transmission electron microscopy, and in two cases by immunofluorescence. There was both intra-alveolar and interstitial eosinophilic pneumonia with bronchiolitis obliterans, microgranulomata, and a vasculitis. Electron microscopy showed numerous eosinophils, many degranulated, and macrophages with phagocytosed eosinophilic granules and intracytoplasmic inclusions. In one case IgM, IgG, and IgA were demonstrated in the bronchial walls and interstitium. No IgE or complement was present. We believe that eosinophil granules are responsible for the tissue damage and fever and suggest mechanisms for this and for the response to steroid therapy.